A metal-organic framework based on Co(II) and 3-aminoisonicotinate showing specific and reversible colourimetric response to solvent exchange with variable magnet behaviour. (June 2022) - Pajuelo-Corral, O.; Pérez-Yáñez, S.; Vitorica-Yrezabal, I.J.; Beobide, G.; Zabala-Lekuona, A.; Rodríguez-Diéguez, A.; Seco, J.M.; Cepeda, J.
Abstract: A versatile metal-organic system consisting of Co-based compounds that show reversible transformations between a 3D metal-organic framework (MOF) of {[Co(μ-3isoani)2 ]·DMF}n (1 ) formula (where 3isoani = 3-aminoisonicotinato and DMF = dimethylformamide) and a 0D monomeric [Co(3isoani)2 (H2 O)4 ] (2 ) complex is reported. These 1 ↔ 2 transformations, triggered by the exposure of the MOF and the monomer-based compound to H2 O and DMF, respectively, involve colour changes from purple (in MOF 1 ) to light brown (in monomeric complex 2 ), which imbues the system with colourimetric sensing capacity towards these solvents. Despite the high reactivity of the MOF in contact with water, it presents good thermal stability and permanent porosity with a remarkably high CO2 capture capacity at room temperature (3.35 mmol/g), which is further analysed by in situ single-crystal X-ray diffraction. Experimental magnetic properties and CASSCF/NEVPT2 calculations of all compounds reveal distinct slow magnetic relaxations for 3D and 0D compounds. Graphical abstract: Two solvent-triggered interchangeable compounds are presented with colourimetric sensing capacity towards water and formamide derivatives, respectively, which additionally modulates their single-molecule magnet behaviour. Moreover, the MOF exhibits good CO2 capture capacity. Image 1 Highlights: Two Co II /3-aminoisonicotinate–based compounds, consisting of a MOF and an isolated complex are interchangeable on solvent exposure. The compounds compose a versatile system behaving as a colourimetric sensor able to detect both dimethylformamide and water. The MOF shows good CO2 gas uptake capacity, and adsorption processes have been studied by in situ single-crystal X-ray diffraction. Both compounds exhibit field-induced SMM behaviour with different relaxation dynamics.